Predominantly extraaxial astroblastoma: imaging and proton MR spectroscopy features. - Baka, J J; Patel, S C; Roebuck, J R; Hearshen, D O (American Journal of Neuroradiology, 1993)
The CT, angiographic, MR, and proton MR spectroscopy findings in a case of astroblastoma, a rare neoplasm of glial cell origin, are presented. Of particular interest is the predominantly extraaxial location of the tumor. CT and MR demonstrated a complex mass consisting of a solid nodule and a peripheral septated cystic component. The extraaxial nature of the mass was suggested on MR.